Bank Regulation and Supervision : What Works Best? - Barth, James R.; Caprio, Gerard, Jr.; Levine, Ross (World Bank, Washington, DC, 2014)
The authors draw on their new database on bank regulation and supervision in 107 countries to assess different governmental approaches to bank regulation and supervision and evaluate the efficacy of different regulatory and supervisory policies. First, the authors assess two broad and competing theories of government regulation: the helping-hand approach, according to which governments regulate to correct market failures, and the grabbing-hand approach, according to which governments regulate to support political constituencies. Second, they assess the effect of an extensive array of regulatory and supervisory policies on the development and fragility of the banking sector. These policies include the following: Regulations on bank activities and the mixing of banking and commerce. Regulations on entry by domestic and foreign banks. Regulations on capital adequacy. Design features of deposit insurance systems. Supervisory power, independence, and resources; stringency of loan classification; provisioning standards; diversification guidelines; and powers to take prompt corrective action. Regulations governing information disclosure and fostering private sector monitoring of banks. Government ownership of banks. The results raise a cautionary flag with regard to reform strategies that place excessive reliance on a country's adherence to an extensive checklist of regulatory and supervisory practices that involve direct government oversight of and restrictions on banks. The findings, which are much more consistent with the grabbing-hand view of regulation than with the helping-hand view, suggest that the regulatory and supervisory practices most effective in promoting good performance and stability in the banking sector are those that force accurate information disclosure, empower private sector monitoring of banks, and foster incentives for private agents to exert corporate control.